Moelleriella simaoensis, a new entomogenous species of Moelleriella (Clavicipitaceae, Hypocreales) from Southwestern China - Yang, Zhi-Li; Wang, Zhi-Qin; Ma, Jin-Mei; Yu, Hong (Phytotaxa, 2023)
A new species of Moelleriella, described as Moelleriella simaoensis from Pu’er City, Yunnan Province, was discovered during a diversity survey of entomopathogenic fungi in Southwestern China. It was characterized by producing brightly colored and thin-pulvate stromata, subglobose to ovoid perithecia, cylindrical asci, disarticulating part-spores inside the ascus, and fusiform conidia. Both anamorphic and teleomorphic states were most often found on the same stroma, and the orange conidiomata were aggregated in the center of the stroma. Conidiomata were widely open with several locules per stroma. Multigenes phylogenetic analyses based on nrLSU, tef-1α and rpb1 sequences showed that this species formed a distinct clade and was closely related to Moelleriella puerensis and Moelleriella raciborskii. The Description and illustration of the new species were provided in the present study.